2018
DOI: 10.1007/s10658-018-1540-6
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous plant metabolites against insects

Abstract: Herbivorous insects are responsible for large losses to agriculture through feeding damage itself but also by vectoring pathogens such as viruses. Plants have evolved various mechanisms to defend themselves against insects, including the production of specialised metabolites that act as natural insecticides. Throughout history, plants and plant extracts harbouring specialised metabolites have been exploited by man for their antiinsect properties. Also, commercial insecticides are often based on plant-specialis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 265 publications
(261 reference statements)
0
49
0
1
Order By: Relevance
“…On top of regulation by classical TFs, specialized metabolite biosynthesis is likely to involve transcriptional and post‐transcriptional silencing, that is regulation via endogenous small non‐coding RNAs (sRNAs). Although a substantial number of sRNAs has been computationally predicted to target genes in specialized metabolic pathways, very few have so far been experimentally validated (Kortbeek et al ., ). microRNAs (miRNAs), although quantitatively by far a minor type amongst the total of small RNAs encountered, have been studied most extensively.…”
Section: Regulation Of Voc Biosynthesismentioning
confidence: 97%
See 1 more Smart Citation
“…On top of regulation by classical TFs, specialized metabolite biosynthesis is likely to involve transcriptional and post‐transcriptional silencing, that is regulation via endogenous small non‐coding RNAs (sRNAs). Although a substantial number of sRNAs has been computationally predicted to target genes in specialized metabolic pathways, very few have so far been experimentally validated (Kortbeek et al ., ). microRNAs (miRNAs), although quantitatively by far a minor type amongst the total of small RNAs encountered, have been studied most extensively.…”
Section: Regulation Of Voc Biosynthesismentioning
confidence: 97%
“…A plethora of natural specialized metabolites is described in the literature for their potential in replacing chemicals. There are, however, only a handful of examples of such endogenously produced metabolites validated in planta , let alone in a field situation (Isman and Grieneisen, ; Kortbeek et al ., ).…”
Section: Agricultural Importance Of Vocsmentioning
confidence: 97%
“…The exploration of endogenous plant resistance mechanisms against herbivory is a promising and effective alternative that can reduce the use of chemical pesticides (Kortbeek, van der Gragt, & Bleeker, ; Paixão et al, ). An important resistance mechanism of plants against herbivores is mediated by the lipoxygenase pathway, which produces intermediates used by the octadecanoid pathway to synthesize jasmonic acid, a phytohorme that controls the expression of defensive metabolites, such as protease inhibitors (Meriño‐Cabrera et al, ; Woldemariam, Ahern, Jander, & Tzin, ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…To ascertain whether other saponins would similarly inhibit conidia germination and appressorium formation, we used the in vitro assays to test two closely related saponins, Hedegeranin, and Oleanolic acid. Despite their reported insecticidal effects (23, 24), we found that washing conidia with 5-100 nM/L of Hedegeranin or Oleanolic acid did not adversely affect conidia germination and appressorium morphogenesis of P oryzae in vitro (Figure.3 E, F, and G). Together, these findings suggest that glycosylated Bayogenin, such as the Bayogenin 3-O-cellobioside, and Bayogenin 3-O-β-D-glucopyranoside are potent phytochemicals that specifically inhibit infectious development of P oryzae .…”
Section: Resultsmentioning
confidence: 63%